2007
DOI: 10.1523/jneurosci.0117-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinase 2 (ERK2) Knockdown Mice Show Deficits in Long-Term Memory; ERK2 Has a Specific Function in Learning and Memory

Abstract: The extracellular signal-regulated kinase (ERK) 1 and 2 are important signaling components implicated in learning and memory. These isoforms display a high degree of sequence homology and share a similar substrate profile. However, recent findings suggest that these isoforms may have distinct roles: whereas ERK1 seems to be not so important for associative learning, ERK2 might be critically involved in learning and memory. Thus, the individual role of ERK2 has received considerable attention, although it is ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 58 publications
3
133
0
Order By: Relevance
“…Drd2-EGFP, Drd1a(EY262)-Cre, Drd2(EY43)-Cre, and Adora2a-Cre mice were purchased from the Mutant Mouse Regional Resource Center (MMRRC) (Gong et al, 2007). Erk1 Ϫ / Ϫ (Mapk3 Ϫ / Ϫ ) and Erk2 loxP/loxP (Mapk1 loxP/loxP ) mice (Nekrasova et al, 2005;Samuels et al, 2008) were kindly provided by G. Landreth (Case Western Reserve University, Cleveland, OH). Drd1a tdTomato (Ade et al, 2011), Ai3-EYFP, and Ai9-tdTomato (Madisen et al, 2010) reporter lines were purchased from The Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drd2-EGFP, Drd1a(EY262)-Cre, Drd2(EY43)-Cre, and Adora2a-Cre mice were purchased from the Mutant Mouse Regional Resource Center (MMRRC) (Gong et al, 2007). Erk1 Ϫ / Ϫ (Mapk3 Ϫ / Ϫ ) and Erk2 loxP/loxP (Mapk1 loxP/loxP ) mice (Nekrasova et al, 2005;Samuels et al, 2008) were kindly provided by G. Landreth (Case Western Reserve University, Cleveland, OH). Drd1a tdTomato (Ade et al, 2011), Ai3-EYFP, and Ai9-tdTomato (Madisen et al, 2010) reporter lines were purchased from The Jackson Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacological inhibition of ERK signaling prevented consolidation of motor skill learning, instrumental learning, and habit formation (Bureau et al, 2010;Shiflett et al, 2010;Shiflett and Balleine, 2011). In contrast, loss of ERK1 in germline knock-out mice showed surprising effects, including baseline hyperactivity, increased synaptic plasticity, enhanced learning, and enhanced locomotor response to cocaine (Selcher et al, 2001;Mazzucchelli et al, 2002;Ferguson et al, 2006;Engel et al, 2009). This disparity has been attributed to increased ERK2 function in ERK1-deleted animals, emphasizing the need to delete both ERK1 and ERK2 in genetic studies (Mazzucchelli et al, 2002;Ferguson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…P32 rats exposed to isoflurane on P7 were subjected to open-field test as previously described [19]. The behavior of the rats in the novel environment was noted as the movement of the rats in the open field.…”
Section: Open-field Testmentioning
confidence: 99%
“…In order to evaluate anxiety-related behaviour, the elevated plus-maze test was conducted as described by Satoh et al [19]. The apparatus used for the test consisted of two open (25 x 5 cm) and two enclosed arms.…”
Section: Elevated Plus-maze Testmentioning
confidence: 99%
“…However, the mutant mice displayed significant impairment in context-, but not cue-, elicited freezing when tested 24 hours later. Recently, a separate group reported that full ERK2 KO mice show almost a 100% prenatal mortality rate, thus used a specific ERK2 mutant mouse with partially reduced (20-40%) ERK2 (Satoh et al, 2007). Those ERK2 mutant mice showed the same ERK1 level, anatomy and synaptic density as wildtypes.…”
Section: The Role Of Mapk In the Acquisition Of Conditioned Fearmentioning
confidence: 99%